Perlindungan Hukum Terhadap Pelaku Tindak Pidana Pembunuhan karena Pembelaan Terpaksa yang Melampaui Batas (Noodweer Exces) - Ayu Putri Arisandy; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2024)
In everyday life, a person often becomes a victim of crime in the form of other people's crimes. Protection goes beyond these boundaries, so law enforcement is used against criminals to protect their rights. Forced defense cross-border criminals are often prosecuted for crimes they have committed, even if the criminals act in self-defense. Referring to the problems above, the formulation of the problems discussed are: 1). To what extent do the legal arrangements for the criminal act of compulsory defense go beyond the limits? 2). What is the legal protection for perpetrators of cross-border crimes in forced defense? Discussions were held on the formulation of questions. Namely: 1. Legislative provisions regarding extrajudicial criminal defense actions are regulated in Article 49 paragraph (1) of the Criminal Code and are clearly defined in Section 49 paragraph (2) of the Criminal Code. Basically, being forced to defend against attacks. 2. The form of legal protection for the perpetrators of the crime of murder is contained in article 338 of the Criminal Code and is an additional mandatory defense to article 49 paragraph 2 of the Criminal Code.